Pengaruh Pengetahuan Fiskal dan Ketegasan Sanksi Terhadap Kepatuhan Pajak Pelaku UMKM Pajak Restoran di Kota Gorontalo - Ayub Domili; Lukman Pakaya; Muliyani Mahmud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the effect of fiscal knowledge and strictness of sanctions on tax compliance of restaurant tax MSMEs in Gorontalo City. The research method used was quantitative. Data collection was conducted by distributing questionnaires to restaurant tax MSMEs in Gorontalo City. The population in this study were restaurant tax MSMEs registered as restaurant taxpayers in Gorontalo City, with a sample size of 92 respondents. The data analysis technique used was multiple linear regression analysis with the help of SPSS. The results showed that fiscal knowledge partially had a positive and significant effect on tax compliance of restaurant tax MSMEs in Gorontalo City, and strictness of sanctions had a positive and significant effect on tax compliance of restaurant tax MSMEs in Gorontalo City. Simultaneously, fiscal knowledge and strictness of sanctions had a positive and significant effect on tax compliance of restaurant tax MSMEs in Gorontalo City, explained by the variable's R-square value of 74.2%, while the remaining 25.8% was contributed by other variables outside the research model.